Exploration of lactic acid bacteria from husk and black rice (Oryza sativa L) of toraja origin - Hapiwaty, Saldi; Zainal, Tuti Handayani; Abidin, Hamdayani Lance; Utami, Yuri Pratiwi (STKIP Persada Khatulistiwa Sintang, 2025)
Lactic acid (LAB) is a bacteria involved in food fermentation and can be used as a probiotic to provide health benefits for those who consume it. This research aims to bring innovation and added value, and improve the community's utilization of probiotics (LAB) from husks and black rice from Toraja. The method used is collecting and processing samples, isolation and purification of LAB, microscopic and macroscopic identification, testing the activity/potential of LAB (Kirby Bauer), and molecular identification of 16S rRNA (sequencing). This study has confirmed that fermented rice has Lactococcus taiwanensis type lactic acid bacteria, while fermented husk is not a type of lactic acid bacteria. Lactococcus taiwanensis bacteria have probiotic potential and can produce antibacterial substances.